Enhanced tolerance against a fungal pathogen, Fusarium oxysporum f.sp. cubense (race 1) in transgenic silk banana - Subramaniam, Sreeramanan; Mahmood, Maziah; Rosli, N. M.; M., Sariah; Rathinam, Xavier (Academic Journals, 2006)
An effective method has been developed for the stable transformation and regeneration of silk banana (Musa spp. AAB group) cv `Rastali` using microprojectile bombardment. Recent progress with advanced in vitro cultures of banana such as establishment of highly regenerable tiny single meristem buds opened the opportunity for the production of disease tolerant transgenic bananas. Chitinase and glucanase the important disease tolerant genes were successfully transformed into banana using microprojectile bombardment system together with gfp and gusA genes as reporter gene. Proliferating single buds were selected on geneticin G-418 to produce a number of putatively transformed bananas. Five different treatments using different chitinase and glucanase genes inserted singly or in combination were carried out. Molecular analyses such as Polymerase Chain Reactions (PCR) and Southern blot was performed to confirm the integration and expression of the introduced genes in genome. The transgenic banana plantlets from each treatment inoculated with conidial suspension of fungal to evaluate the degree of tolerance and to investigate the effectiveness of the bioassay system as a potential tool for early screening. Different chemical compound such as hydrogen peroxide (H2O2) and relevant enzyme activities such as Phenylalanine Ammonia Lyase (PAL), chitinase, β-1,3-glucanase, peroxidase (PER) and polyphenol oxidase (PPO), were determined for each treatment including control plantlets. Evaluation of disease development in primarily and secondary infections showed that combination of the two transgenes gave substantially greater protection against the fungal than single-transgene introduction. Productive interactions between chitinase and glucanase transgenes in planta point to combinatorial expression of antifungal genes as an effective approach to enhanced tolerance to Fusarium wilt disease.